A Case Study On Profitability Analysis Of Vijayawada Tollway Private Ltd (Vtpl). - KATURI, PHANI KUMAR.; KUMAR, K.S. VENKATESWARA; PUTTA, HARIKA. (The journal of contemporary issues in business and government, 2021)
The economic development of any country road infrastructure plays a vital role. Originally public infrastructure like roads has been financing from central budgetary recourses. Because of revenue deficit state and central governments are unable to fund for construction of road infrastructure projects. To a given period of time,the private sector has been increased the financing and construction of road infra projects. The development of road infrastructure projects various forms of Public-Private Partnerships(PPPs) have been used extensively. For implementation of any infrastructure toll road projects financial feasibility or sustainability has been a leading issue. This case study is based on project financial risks at public-private partnership delivery, especially under a build operate transfer (BOT) model. The main purpose of this study is to undertake an integrated profitability appraisal of an existing PPP toll road project in the South Indian state of Andhra Pradesh by using the Cost-Benefit Analysis (CBA) method.